FAKTOR–FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI PEMERINTAHAN (Study kasus pada Dinas Pemberdayaan perempuan, Perlindungan Anak, Pengendalian Penduduk dan Keluarga Berencana Kabupaten Way Kanan) - M. Nasir (STIE Trisna Negara OKU Timur, 2022)
This study aims to explain the factors that affect employee performance. This research using a quantitative method where the explanation is objective by explaining the existing approach. This study used 21 research respondents. There are three variables, that is: 2 (two) independent variables and 1 (one) dependent variable where technical competence and environmental influences as independent variables and employee performance as dependent variable. The result of this study showed that: (1) There is an influence of technical competence on employee performance, with a level of influence (R-square) of 17,6%, (2) there is an influence of environmental influences on employee performance, with an influence level of 30,7 %, and (3) there is an influence between technical competence and environmental influences on employee performance, with an influence level of 37,4 %.Keyword: Technical Competence, Environmental Influences, Employee Performance